PRODUCTIVITY OF DIATOMS IN CULTURE AND IN MARINE HABITATS - Werner, Dietrich; Roth, Richard (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
The diatom dominated phytoplankton net primary production in different areas of the ocean (from 100-1000 mg C. m-2. day-1) and in estuaries (up to 2000 mg C. m-2. day-1) is compared with the maximum productivity of marine diatoms in culture (50 g C . m-2 . day-1) for Cyclotella cryptica (Centrales, Diatomeae) and 1000 mg C . m-2. day-1 for Coscinodiscus asteromphalus (Centrales, Diatomeae). The rate of C-assimilation as a measure of primary production is critically discussed in relation to the different factors regulating the reproduction of cells and the production of organic material. The evaluation of another parameter for primary production: light dependent protein synthesis (LPS) is proposed, which brings reproduction of phytoplankton cells and the production of organic material closer together. As an example of the requirement for more information about the potential growth and production rate of diatom species, some results on the cultivation of the tropical shallow water diatom Bellerochea yucatanensis V. STOSCH (Centrales, Diatomeae) are presented. At 30 C this species has a specific growth rate (µ max) of = 4.4 divisions per day and 4 divisions per day at 34°C with an average cell size of 34 x 26 ? m. The temperature range of this species is from 12°C (µ = 0.3) to 35°C (µ = 2).